Ecological study on mangrove forest in East Coast of North Sumatra - ONRIZAL ONRIZAL; CECEP KUSMANA (Society for Indonesian Biodiversity, 2008)
Ecological studies on mangrove forest in East Coast of North Sumatra have been carried out with field work in transect method and laboratory analyses. This study would be covered on floristic composition, abrasion, green belt, soil properties, and water quality of mangroves. Land system map and landsat TM imagery (year 1996 coverage) as main material in this study were used and overlay to determine training area. Based on vegetation inventory found that 20 mangrove species and by vegetation analyses, we known that Avicennia marina was as dominant tree species of seedling and sapling stage. Tree stage was not found in the area, yet. Environment properties of the mangrove area were suitable for mangrove growth and rehabilitation with the exception of pyrite content in the mangrove soil. Average of mangrove green belt was 25 m with range from 10 to 80 m in KJP (Kajapah) land system and 30 m with range 10 to 50 m in PTG (Putting) land system. Abrasion rate in the area was very high, i.e. 6 m per year in KJP land system, and 10 m per year in PTG land system.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: mangrove, abrasion, green belt, soil properties, water quality, North Sumatra